Faktor yang Berpengaruh terhadap Imunisasi Dasar Lengkap (IDL) pada Bayi - Maria Ferdinanda Bukan; Pius Weraman; Imelda Manurung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the factors influencing Complete Basic Immunization (IDL) in infants in Kupang City in 2021. The method used is analytic descriptive with a cross-sectional design. The data obtained were analyzed using the chi-square test. The results showed that the factor of vaccine availability obtained a p-value of 0.000, the completeness of immunization equipment was 0.038 and the vaccine expiration date was 0.121. In conclusion, there is a significant relationship between the completeness of immunization kits and vaccine availability on IDL coverage in Kupang City in 2021. Keywords: Infant, Complete Basic Immunization